Relationship between macronutrients and energy intake and liver serum transaminase levels in elderly athletes and non-athletes: findings from the Neyshabur longitudinal study on aging - Hossein Taghizadeh Bilondi; Seyyed Mostafa Arabi; Fatemeh Mohammadzadeh; Seyed Reza Mirhafez; Alireza Ostadrahimi (BMC Geriatrics)
Abstract Background Assessing liver health and its determinants in the elderly is crucial. Lifestyle factors, including nutrition and exercise, may influence liver function. This study aimed to investigate the association between macronutrients and energy intake with serum levels of aminotransferases in elderly Iranian athletes and non-athletes. Methods A cross-sectional study involving 811 elderly participants (369 athletes, 442 non-athletes) from the Neyshabur Longitudinal Study on Aging (NeLSA) was conducted. Dietary intake was assessed using a food frequency questionnaire. Serum Alanine aminotransferase (ALT) and aspartate aminotransferase (AST) levels were measured. Regression analyses were employed to evaluate the associations between macronutrient intake and liver enzymes, adjusting for potential confounding variables. Results In elderly athletes, higher calorie, protein, and carbohydrate intake were significantly associated with elevated ALT levels (p < 0.01 for all). Additionally, higher carbohydrate and calorie intake were linked to increased AST levels in athletes (p < 0.05 for both). For elderly non-athletes, only higher protein intake was significantly associated with increased ALT levels (p < 0.05), while no nutritional factors were associated with changes in AST levels. Conclusions This study revealed that higher calorie, protein, and carbohydrate intake were associated with elevated ALT and AST levels in elderly individuals, particularly athletes. For athletes, all three nutrients were linked to elevated ALT, while only carbohydrates and calories impacted AST. For non-athletes, only protein affected ALT. These findings suggest that tailored nutritional strategies may be necessary to preserve liver health in active aging populations.